2019
DOI: 10.1016/j.atherosclerosis.2018.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) as a risk factor for calcific aortic valvulopathy in heterozygous familial hypercholesterolemia

Abstract: (a) levels above 30-50 mg/dL associate with calcific aortic valve stenosis. • he-FH patients have marked lifelong elevation of serum LDL-cholesterol level. • AVC among he-FH patients is more frequent than in the general population. • Lp(a) life years is a useful metric of cumulative burden of Lp(a). • Apo(a) antisense oligonucleotides effectively lower Lp(a) concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Compelling evidence from traditional epidemiological, genome-wide association, and Mendelian randomization studies has revealed that elevated plasma Lp(a) level increases the risk of acute myocardial infarction (AMI), ischemic stroke, calcific aortic valve disease, and peripheral arterial disease in non-FH patients [ 38 ]. Elevated lipoprotein (a) was found to be a significant CVD risk factor in HeFH [ 39 ], and Lp(a) level above 50 mg/dL is recently found to be an independent risk factor for calcific aortic valvulopathy among HeFH patients [ 40 ]. Safety analysis demonstrated that PCSK9-mAbs showed good safety, and the incidence of common and serious adverse reactions was basically the same as that of the placebo group in addition to abnormal liver function risk.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence from traditional epidemiological, genome-wide association, and Mendelian randomization studies has revealed that elevated plasma Lp(a) level increases the risk of acute myocardial infarction (AMI), ischemic stroke, calcific aortic valve disease, and peripheral arterial disease in non-FH patients [ 38 ]. Elevated lipoprotein (a) was found to be a significant CVD risk factor in HeFH [ 39 ], and Lp(a) level above 50 mg/dL is recently found to be an independent risk factor for calcific aortic valvulopathy among HeFH patients [ 40 ]. Safety analysis demonstrated that PCSK9-mAbs showed good safety, and the incidence of common and serious adverse reactions was basically the same as that of the placebo group in addition to abnormal liver function risk.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercholesterolemic LDLr −/− ApoB 100/100 mice are not only a model of CAVD but also a relevant model for human FH. Most (90%) FH patients have a mutation in the LDLr gene, whereas only a minority of patients have mutations in the apolipoprotein-B or PCSK9 genes that are associated with high cholesterol levels already in utero 38 . Since FH patients have a higher risk of developing CAVD, our study suggests that FH patients might be more vulnerable to the hyperlipidemic side effects of vitamin K. In our study, we used MK4, which is an active metabolite of vitamin K1 and is present in meat, cheese and eggs 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cells express a variety of apolipoprotein receptors, in primis the receptor for ApoA1 and B as demonstrated by the hypocholesterolemia and reduced levels of circulating ApoA1 and B expressed by patients with the acquired erythrocytosis Polycythemia Vera (Fujita et al, 2012). Given the great number of RBCs present in the circulation, these receptors are efficient lipid scavengers contributing to maintain the lipid content of the plasma within physiologic levels preventing atherosclerosis and kidney malfunctions (Wahl et al, 2016; Saraf et al, 2017; Vuorio et al, 2018). The effects on erythroblast expansion sustained by VLDL and LDL described in this study suggests that, in addition to exerting scavenger functions, the lipoprotein receptors expressed by erythroid cells tune lipid availability to prevent possible membrane abnormalities due to impairment of lipid metabolism induced by Dex in RBCs produced under conditions of erythroid stress.…”
Section: Discussionmentioning
confidence: 99%